2022
DOI: 10.1038/s41556-022-00949-1
|View full text |Cite
|
Sign up to set email alerts
|

A p53–phosphoinositide signalosome regulates nuclear AKT activation

Abstract: The tumor suppressor p53 and the phosphoinositide 3-kinase (PI3K)-Akt pathway have fundamental roles in regulating cell growth, apoptosis and are frequently mutated in cancer. Here, we show that genotoxic stress induces nuclear Akt activation by a p53dependent mechanism that is independent from the canonical membrane-localized PI3K-Akt pathway. Upon genotoxic stress a nuclear p53-PI3,4,5P3 complex is generated in regions devoid of membranes by a nuclear PI3K, and this complex recruits all the kinases required … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 73 publications
3
70
0
Order By: Relevance
“…The phosphatase-inactivating mutation of PTEN, such as G129R and C124S, enhances the ability of PTEN nuclear import in response to IR [ 34 ]. Another study also confirmed that PTEN knockdown increases nuclear p-Akt [ 69 ], which may indicate that the reduction in nuclear PTEN increases DNA repair and leads to p-Akt nuclear transport. However, the interconnected determination of nuclear import by mono- or poly-ubiquitylation modification is still unclear.…”
Section: Discussionmentioning
confidence: 71%
“…The phosphatase-inactivating mutation of PTEN, such as G129R and C124S, enhances the ability of PTEN nuclear import in response to IR [ 34 ]. Another study also confirmed that PTEN knockdown increases nuclear p-Akt [ 69 ], which may indicate that the reduction in nuclear PTEN increases DNA repair and leads to p-Akt nuclear transport. However, the interconnected determination of nuclear import by mono- or poly-ubiquitylation modification is still unclear.…”
Section: Discussionmentioning
confidence: 71%
“…RNA-seq results indicated that the P53 downstream pathway was significantly enriched in the differentially expressed genes contained in Part II ( Figure S4C ). Mutations in P53 have been reported leading to the activation of AKT/VEGFR signal cascade in some cancers [ 28 , 29 ]. We found the protein expression level of the VEGFR signal pathway suppressed in normal esophageal epithelial cells after long-term exposure to ABS or BS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular endothelial growth factor ( VEGF ) can stimulate the proliferation of endothelial cells by interacting with VEGFR , which plays a vital role in tumor proliferation and metastasis [ 38 , 39 ]. P53 mutants showed activation of AKT/VEGFR signal cascade [ 28 , 40 ]. Our study showed that prolonged exposure to bile acid treatment downregulated the phosphorylation of AKT and expression of VEGFR in P53 -proficient esophagus epithelial cells ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genes that have been differentially modulated are associated with pathways, including p53 signaling pathway, PI3K-Akt signaling pathway, HIF-1 signaling pathway, Hippo signaling pathway, TNF signaling pathway, chemokine ligand 12 signaling pathway, and cytokine production; moreover, retinol metabolism, carbon metabolism, glycolysis, gluconeogenesis, and primary bile acid biosynthesis related with cancer also changed in the two clusters. Previous studies had showed that p53 signaling pathway, PI3K-Akt signaling pathway, HIF-1 signaling pathway are important pathways involved in tumor development and metastasis ( 22 , 23 ). Additionally, glycolysis, gluconeogenesis, and bile acid biosynthesis also play an important role in the tumor progression ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%